(untitled) (MAP Kinase, 2015)
Fungal infections contribute substantially to human suffering and mortality. The interaction between fungal pathogens and their host involves the invasion and penetration of the surface epithelium, activation of cells of the innate immune system and the generation of an effective response to block infection. Numerous host-cell signaling pathways are activated during fungal infection. This review will focus on the main fungal pathogens Aspergillus fumigatus, Candida albicans and Cryptococcus neoformans and their ability to activate the host MAP-kinase signaling pathways leading to cytokine secretion, increased cell motility and killing of the pathogen. Both epithelial and innate immune cells specifically recognize fungal antigens and in particular cell surface polysaccharides such as β-glucans and react to them by activating multiple signaling pathways, including those containing MAP-kinase modules. Recent findings suggest that the host response to fungal infection utilizes the MAP-kinase pathway to differentiate between commensal and pathogenic fungi to selectively react only to the pathogenic forms. However, the paucity of relevant publications strongly emphasize that our understanding of host MAP-kinase signaling in response to fungal infection is still at a very early stage. It is clear, based on studies of host MAP-kinase signaling during viral and bacterial infections, that in fungi as well, a wealth of exciting findings await us.